Risk as a process: a history informed hazard planning approach applied to the 2018 post-fire debris flows, Montecito, California - Serra-Llobet, Anna; Radke, John; Kondolf, G. Mathias; Gurrola, Larry; Rogers, J. David; Lindbergh, Sarah; Douvinet, Johnny (Frontiers in Environmental Science, 2023)
Historical information about floods is not commonly used in the US to inform land use planning decisions. Rather, the current approach to managing floods is based on static maps derived from computer simulations of the area inundated by floods of specified return intervals. These maps provide some information about flood hazard, but they do not reflect the processes involved in creating a flood disaster, which typically include increased exposure due to building on flood-prone land, nor do they account for the greater hazard resulting from wildfire. We developed a method that can be used widely, to analyze how exposure has evolved in flood hazard zones in Montecito, California, an area devastated by debris flows in January 2018, and better understand the nature of the hazard they are exposed to. This method allows us to look at risk as a dynamic process influenced by physical and human factors, instead of a static map. Results show that floods after fires, in particular debris flows and debris laden floods, are very common in Montecito (14 events in the last 200 year), and that despite policies discouraging developments in hazard areas, developments in hazard zones have increased substantially since Montecito joined the National Flood Insurance Program in 1979. We also highlight the limitation of using conventional Flood Insurance Rate Maps (FIRMs) to manage land use in alluvial fan areas such as Montecito. The knowledge produced in this project can help the Montecito community better understand how they came to be vulnerable to floods and inform what actions are they taking now that might increase or reduce their vulnerability to the next big flood.